Chemoenzymatic Assembly of Mammalian O‐Mannose Glycans. (25th June 2018) - Meng, Caicai; Sasmal, Aniruddha; Zhang, Yan; Gao, Tian; Liu, Chang‐Cheng; Khan, Naazneen; Varki, Ajit; Wang, Fengshan; Cao, Hongzhi
Abstract: O‐Mannose glycans account up to 30 % of total O‐glycans in the brain. Previous synthesis and functional studies have only focused on the core M3 O‐mannose glycans of α‐dystroglycan, which are a causative factor for various muscular diseases. In this study, a highly efficient chemoenzymatic strategy was developed that enabled the first collective synthesis of 63 core M1 and core M2 O‐mannose glycans. This chemoenzymatic strategy features the gram‐scale chemical synthesis of five judiciously designed core structures, and the diversity‐oriented modification of the core structures with three enzyme modules to provide 58 complex O‐mannose glycans in a linear sequence that does not exceed four steps. The binding profiles of synthetic O‐mannose glycans with a panel of lectins, antibodies, and brain proteins were also explored by using a printed O‐mannose glycan array.